About the Creation of a Film Noir Canon - Sullà, Enric (452ºF, 2010)
It is easier to establish a canon than to analyze its formation process. This article attempts to explain how the film noir canon was formed using the distinction between the corpus or catalog, the whole of the films, and the canon, the masterpieces. These have constituted the models, upon which, like in a constellation, the academics have attempted to gauge the distinctive features of the lot in the thematic, narrative and stylistic orders. A critical construction in the end, there is not agreement about if film noir is a genre at the theoretical level, either a series or a cycle of the American cinema, but its existence is undeniable at the empirical level.